Intestinal anastomosis : current techniques - Birchard, S. J.; Bright, Ronald M.; Purdue University. School of Veterinary Science and Medicine; American Animal Hospital Association; Pitman-Moore, Inc. (Lafayette, Ind. : Purdue University, School of Veterinary Medicine, 1980)
Discusses diseases of the intestine requiring surgical manipulation due to obstruction by foreign bodies or more serious diseases such as intussusception, vovulus, or torsion.
Slides mounted in 1 carousel.
"A Pitman-Moore continuing educational program."
Produced in cooperation with the American Animal Hospital Association.
Keywords: Veterinary surgery; Veterinary gastroenterology